Carbon black/electrolyte interface study by electromagnetic and electrochemical techniques in γAl2O3/poly(vinylidene fluoride)/carbon black composite materials: Application for lithium-ion batteries. (1st January 2023) - Gauthier, Nicolas; Agrawal, Anshuman; Dubrunfaut, Olivier; Franger, Sylvain; Lestriez, Bernard; Badot, Jean-Claude; Assaud, Loïc
Abstract: This work aims at better understanding the interactions existing between the liquid electrolyte and the solid composite electrode in a Li-ion battery. We substituted the common active material (e.g. LiNi1/3 Mn1/3 Co1/3 O2 or LiFePO4 ) by an insulating (inactive) γ-Al2 O3 compound in order to detect and evidence the interaction between the carbon black electronic additive and the liquid electrolyte. Our study presents the characterization of charge (electrons and ions) transport at different scales by combining a high-frequency analysis performed by broadband dielectric spectroscopy (BDS, up to 10 10 Hz), along with a low-frequency analysis performed by electrochemical impedance spectroscopy (EIS, down to 10 −3 Hz). Two carbon black materials with two different specific surface areas (80 m 2 .g −1 and 65 m 2 .g −1, respectively) were studied. The electronic percolation threshold and the kinetics of impregnation of the hierarchical composite electrode by the liquid electrolyte have been determined with respect to the carbon black content. The significant influence of the adsorbtion of ions at the carbon black surface on the electrons transport is particularly highlighted and explained.